IMPLEMENTATION OF INNOVATIVE TECHNOLOGIES FOR THE TRAINING OF FUTURE SOCIAL WORKERS IN A HIGHER SCHOOL - Крикунова O.В.; Сидорчук, Л.П. (SWorldJournal, 2023)
The main components of educational innovation are defined and characterized. The general laws of innovation processes are presented. The features of the teacher’s professionalism, which provide conditions for self-realization of students in various types